Tips for making business plan presentations (Part II) - Mat Zin, Sakinah; Nik Jaafar, Nik Fazlin Hiryati; Nik Hassan, Nik Fakrulhazri; Ibrahim, Norlaila; Kamaludin, Mohd Ariff; Ismail, Irwan; Md Noor, Jannah Munirah; Jasni, Nur Syuhada; Mohamed Ahmad, Ferozah Haini (Universiti Teknologi MARA, Terengganu, 2019)
The panels want to learn about you as well os your business plan. Perform deep breathing exercises In order to relax prior to going into the room. Smile and present on image of confidence. Be enthusiastic about your business proposal and remember not to rush your presentation.